Productivity Dynamics of Malaysian Banking Institutions - Khong, Roy Wye Leong (2006)
The productivity behaviors play important role in encouraging the profitability of Malaysian banking institutions. Thus, it is important for bank management and banking regulatory authorities to understand the factors that underlying the productivity behaviors of the banking industry. Malmquist productivity index was used to measure the productivity changes of Malaysian commercial banks, finance companies and merchant banks over the period of 1991 to 2003 . The productivity change was also decomposed into technological change and technical efficiency change. In addition, the dynamic panel method based on Generalized Method of Moments was also employed to identify the determinates of total factor productivity. In general, commercial banks, finance companies and merchant banks experienced average positive productivity growth of 2.33%, 1.75% and 3.19% per annum respectively. During the period under study, the growth in productivity for finance companies and merchant banks were attributed to both technological progress and technical efficiency increased. However, commercial banks productivity progress was due solely to technological improvement. A fact worth noting is that all the three types of banking institutions exhibited the dominance of technological progress as the source of productivity growth. In the second stage dynamic panel regression, the results for commercial banks and finance companies were similar in most aspects. In particular, the age of the institutions and the development of the capital market were positively related to the commercial banks and finance companies productivity levels. On the other hand, commercial banks and finance companies that have high specializations of outputs tended to have lower productivity levels. Moreover, the productivity level will increase at a decreasing rate, as the size of finance company increase. Turning to the behaviors of merchant banks, the age of the merchant banks and the two tier regulatory system were the only factors that have adverse effects on the productivity level of merchant banks.